The Nutritional Supplement L-Alpha Glycerylphosphorylcholine Promotes Atherosclerosis - Wang, Zeneng; Hazen, Jennie; Jia, Xun; Org, Elin; Zhao, Yongzhong; Osborn, Lucas J.; Nimer, Nisreen; Buffa, Jennifer; Culley, Miranda K.; Krajcik, Daniel; van den Born, Bert-Jan H.; Zwinderman, Koos; et al. (International journal of molecular sciences, 2021)
L-alpha glycerylphosphorylcholine (GPC), a nutritional supplement, has been demonstrated to improve neurological function. However, a new study suggests that GPC supplementation increases incident stroke risk thus its potential adverse effects warrant further investigation. Here we show that GPC promotes atherosclerosis in hyperlipidemic Apoe−/− mice. GPC can be metabolized to trimethylamine N-oxide, a pro-atherogenic agent, suggesting a potential molecular mechanism underlying the observed atherosclerosis progression. GPC supplementation shifted the gut microbial community structure, characterized by increased abundance of Parabacteroides, Ruminococcus, and Bacteroides and decreased abundance of Akkermansia, Lactobacillus, and Roseburia, as determined by 16S rRNA gene sequencing. These data are consistent with a reduction in fecal and cecal short chain fatty acids in GPC-fed mice. Additionally, we found that GPC supplementation led to an increased relative abundance of choline trimethylamine lyase (cutC)-encoding bacteria via qPCR. Interrogation of host inflammatory signaling showed that GPC supplementation increased expression of the proinflammatory effectors CXCL13 and TIMP-1 and activated NF-κB and MAPK signaling pathways in human coronary artery endothelial cells. Finally, targeted and untargeted metabolomic analysis of murine plasma revealed additional metabolites associated with GPC supplementation and atherosclerosis. In summary, our results show GPC promotes atherosclerosis through multiple mechanisms and that caution should be applied when using GPC as a nutritional supplement.